KONDISI TERUMBU KARANG DI KAWASAN WISATA PULAU BOKORI, KENDARI, PROVINSI SULAWESI TENGGARA - Ofri Johan; Jupri Jupri; Fella Pritian Cera; Ahmad Rezza Dzumalex; Ratna Diyah Palupi; Imam Bactiar (OSEANA, 2021)
Bokori Island has been a tourist destination managed by the Tourism Office of the Southeast Sulawesi Provincial since 2014. The location is close to the city center, making this island visited by many tourists. In addition to the beauty of the island, it is also necessary to maintain the beauty of coral reefs as objects for underwater recreation. The study was conducted on 24–25 July 2019 at three sites of observation. The research purpose was to determine the condition of coral reefs of the island, which is used as a tourist destination. The result indicates that the condition of coral reefs is categorized good by having coral cover about 50.67%. The dominant coral at the island is the foliose coral (CF) group with percent cover about 22%, followed by coral branching (CB) 10%, Acropora tabulate (ACT) 8.57%, mushroom coral (CMR) 6%, encrusting coral (CE) 2% and massive coral (CM) 1.33%. The dominant type of substrate was dead coral with algae (DCA) about 37.3%, and the damage due to explosion could still be seen in the location. The current condition of coral needs to be maintained and improved supervision so that live coral can improve so that the function to support underwater tourism can be achieved.